Pre- and post-COVID-19: The impact of the pandemic and stock market psychology on the growth and sustainability of consumer goods industries - Jan, Naveed; Li, Zeyun; Xiyu, Liu; Farhan Basheer, Muhammad; Tongkachok, Korakod (Frontiers in Psychology, 2022)
The prime objective of the current study is to investigate the impact of Pre-post Covid -19 pandemic and stock market psychology on eight different business units in the Shandong stock market and their subsequent impacts on investor investment decisions. The sample size of the study is consists of 5000 individuals from eight different business units. The results of the study indicated that pre-post covid-19 and stock market psychology have a significant positive impact on investor investment decisions in the consumer appliance, cosmetic and beauty, textiles and apparel industry while the insignificant negative impact on investor investment decision in the sporting, household, consumer electronics, optical photography, household and cleaning industries etc. The results would be significant for Chinese stakeholders as they seek to link practices and outcomes. Chinese stakeholders will understand better the role pre-post covid-19 and psychology of stock market on these eight different business units in Shandong province. This should guide investors to make changes in stock market trading practices to face these challenges to increase their required rate of return from their specific stock market investment decision.